Information Architecture Strategies in the Classroom: How Do Increasingly Complex Digital Ecosystems in Higher Education Shape the Contours of Instructor-Student Communication? - Lahey, Michael (Teaching and Learning Inquiry, 2024)
The proliferation of digital software is an increasingly accepted part of everyday life in higher education in the United States. While this software affords some opportunities, it can create confusing experiences for students as well. In this paper, I ask how might increasingly complex digital ecosystems in higher education shape the contours of instructor-student communication. To answer this question, I conducted an exploratory case study in the form of an online survey (n=83) and subsequent interviews (n=18) with user experience (UX) design students at a large public university in the southeastern United States. The research showed that students felt confusion regarding digital software protocols in their classes, how protocols varied from class to class, an inability to remember when and how to communicate with instructors outside of class, unsureness about where to locate information, and a preference for messaging applications over email. Research results suggest that instructor-student communication in higher education can be productively viewed through the lens of information architecture. In doing so, I argue for the need for instructors to implement strong information architecture strategies that help make sense of information in increasingly complex academic ecosystems. Read the corresponding ISSOTL blog post here.